Federal tax co-participation: a proposal to exit of the current gibberish (Cultura Económica, 2019)
Difficulties to match the political organization of a country with its economic activity become evident in the formulation of its tributary model and particularly in the methods of allocation of its common fiscal resources. In Argentina, the criteria to solve these conflicts have not been the result of an optimizing economic analysis; nor have they been made aiming to overcome regional imbalances. Rather, they have consolidated the status quo, responding to emergency generated disputes. On the other side, there is the risk of proposing solutionsof apparent simplicity and mutual responsibility which imply severe difficulties regarding legal and managing implementation that may generate new asymmetries and conflicts. In this article, the author proposes the elaboration of models of fiscal allocation which harmonize legal technique with economic reality and pursue fairness, efficiency and the responsibility of the actors involved.
Keywords: national constitution; taxation model; potential and real tax collection; federal fiscal organism